Transformation of ginseng saponins to ginsenoside rh2 by acids and human intestinal bacteria and biological activities of their transformants - Bae, Eun-Ah; Han, Myung Joo; Kim, Eun-Jin; Kim, Dong-Hyun (Archives of pharmacal research, 2004)
When ginseng water extract was incubated at 60 degrees C in acidic conditions, its protopanaxadiol ginsenosides were transformed to ginsenoside Rg3 and delta20-ginsenoside Rg3. However, protopanaxadiol glycoside ginsenosides Rb1, Rb2 and Rc isolated from ginseng were mostly not transformed to ginsenoside Rg3 by the incubation in neutral condition. The transformation of these ginsenosides to ginsenoside Rg3 and delta20-ginsenoside Rg3 was increased by increasing incubation temperature and time in acidic condition: the optimal incubation time and temperature for this transformation was 5 h and 60 degrees C resepectively. The transformed ginsenoside Rg3 and delta20-ginsenoside Rg3 were metabolized to ginsenoside Rh2 and delta20-ginsenoside Rh2, respectively, by human fecal microflora. Among the bacteria isolated from human fecal microflora, Bacteroides sp., Bifidobacterium sp. and Fusobacterium sp. potently transformed ginsenoside Rg3 to ginsenoside Rh2. Acid-treated ginseng (AG) extract, fermented AG extract, ginsenoside Rh2 and protopanaxadiol showed potent cytotoxicity against tumor cell lines. AG extract, fermented AG extract and protopanaxadiol potently inhibited the growth of Helicobacter pylori.